Manganese iron phosphate precursor, manganese iron lithium phosphate positive electrode material and preparation method thereof

CN122789362APending Publication Date: 2026-09-22张静
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611102745.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0003]为抑制锰溶出,目前主要采用以下策略:其一是降低材料中锰含量,但此举牺牲了高电压平台的容量贡献,能量密度提升有限;其二是通过镁、钒、钛等元素进行体相掺杂,以增强晶格稳定性,但常规掺杂手段多着眼于宏观组分调整,对锰离子在颗粒内部的空间分布缺乏精确控制,难以针对性地抑制颗粒表面与电解液直接接触区域的锰溶出;其三是表面包覆碳层或氧化物层,虽可在一定程度上阻隔界面反应,但单一包覆层难以解决近表层区域锰的本征化学不稳定性

Benefits of technology

(1)本发明以固液复合法优先原位生成MnPO4作为颗粒富锰内核,通过分阶段补铁构建“核高锰、壳低锰”径向梯度结构。颗粒表层富铁相化学稳定性远高于高锰相,大幅降低充放电过程中Mn3+与电解液接触发生腐蚀溶出的风险,同时内核保留高锰组分维持高电压平台与高能量密度,从根源上破解传统磷酸锰铁锂“高锰高能量”与“锰易溶出循环衰减”的核心矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122789362A_ABST
    Figure CN122789362A_ABST
Patent Text Reader

Abstract

The application provides a manganese iron phosphate precursor, a lithium manganese iron phosphate positive electrode material and a preparation method thereof. The positive electrode material comprises a lithium manganese iron phosphate base body and a carbon layer coated on the surface of the base body, the lithium manganese iron phosphate base body is prepared by lithiumizing solid phase sintering of a radial gradient phosphate precursor, the phosphate precursor takes manganese phosphate phase MnPO4 as an inner core of particles; the content of manganese element in the particles decreases in a gradient from the center to the surface in the radial direction, and the content of iron element increases in a gradient; the base body is spherical secondary particles, presents a bimodal particle size distribution, is composed of large particles with D50=15-25 mu m and small particles with D50=3-8 mu m, and the mass ratio of the large particles to the small particles is (1.5-7):1; the manganese element and the iron element in the base body both exist in a +3 valence state and the molar ratio of the two is 0.99:0.01-0.01:0.99. The application realizes high tap density by constructing a "core high manganese, shell low manganese" radial gradient structure and a MnPO4 rich manganese inner core, inhibiting manganese elution and stabilizing trivalent manganese, combining bimodal grading and multi-element carbon coating, and preparing a positive electrode material with high energy density and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery cathode material technology, and in particular to a core-rich manganese-rich radial gradient manganese iron phosphate precursor, a low-manganese-dissolution high-pressure multi-component carbon-coated manganese iron phosphate cathode material, and its preparation method. Background Technology

[0002] Lithium manganese iron phosphate (LiMn) x Fe 1-x PO4 (LMFP) is used as a cathode material for lithium-ion batteries because it combines the excellent thermal stability of lithium iron phosphate with the higher operating voltage of lithium manganese phosphate (4.1 V vs. Li / Li). + This has become a research hotspot for next-generation high-energy-density energy storage materials. However, this system has long faced two interconnected core technological bottlenecks: one is the high-temperature disproportionation reaction of manganese (2Mn2O3). 3+ →Mn 2+ +Mn 4+ This leads to the instability of trivalent manganese, making it difficult for the material to achieve more than 80% of its theoretical capacity; secondly, during charging and discharging, Mn... 3+ / Mn 2+ Redox reactions, accompanied by Jahn-Teller distortion, cause manganese ions to dissolve and migrate across the interface to deposit on the negative electrode surface, accelerating battery capacity decay and impedance growth. These problems are particularly pronounced with increasing manganese content, directly hindering the development of high-manganese lithium iron phosphate materials.

[0003] To suppress manganese leaching, the following strategies are currently mainly adopted: First, reducing the manganese content in the material, but this sacrifices the capacity contribution of the high-voltage platform, resulting in limited energy density improvement; second, bulk doping with elements such as magnesium, vanadium, and titanium to enhance lattice stability, but conventional doping methods mostly focus on macroscopic composition adjustment, lacking precise control over the spatial distribution of manganese ions within the particles, making it difficult to specifically suppress manganese leaching in the area directly in contact with the electrolyte on the particle surface; third, coating the surface with a carbon layer or oxide layer, which can block interfacial reactions to some extent, but a single coating layer cannot solve the intrinsic chemical instability of manganese in the near-surface region. Furthermore, the industrial preparation of lithium manganese iron phosphate precursors often employs a pure liquid-phase co-precipitation method. Although this method can achieve molecular-level mixing, the co-precipitation rates of divalent manganese and divalent iron differ significantly, easily leading to uneven elemental distribution. Moreover, the oxidation of divalent manganese to trivalent manganese during subsequent high-temperature sintering is insufficient and uncontrollable, exacerbating the disproportionation problem of trivalent manganese in the product. In addition, the compaction density of the finished product also needs further improvement.

[0004] In summary, how to achieve the spatially optimized distribution of manganese elements inside the particles to suppress surface manganese dissolution, stabilize trivalent manganese to avoid disproportionation, and simultaneously improve the compaction density of the material while increasing the overall manganese content of the material is a technical challenge that urgently needs to be solved in the field of lithium manganese iron phosphate cathode materials.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a precursor of manganese iron phosphate, a cathode material of manganese iron lithium phosphate, and a method for preparing the same, thereby solving at least one of the problems mentioned in the background art.

[0007] In a first aspect, the present invention provides a lithium manganese iron phosphate cathode material, comprising a lithium manganese iron phosphate matrix and a carbon layer coated on the surface of the matrix. The lithium manganese iron phosphate matrix is ​​prepared by lithiation solid-state sintering of a radially gradient phosphate precursor. The phosphate precursor has a manganese phosphate phase MnPO4 as the particle core. The manganese content of the particles decreases in a gradient from the center to the surface, while the iron content increases in a gradient. The matrix consists of spherical secondary particles with a bimodal particle size distribution, composed of large particles with D50 = 15~25 μm and small particles with D50 = 3~8 μm, and the mass ratio of large particles to small particles is (1.5~7):1. In the matrix, both manganese and iron exist in the +3 oxidation state and their molar ratio is 0.99:0.01~0.01:0.99.

[0008] A second aspect of the present invention provides a method for preparing the above-mentioned lithium manganese iron phosphate cathode material, comprising the following steps: S1: Mix manganese, iron, and phosphorus sources with water to form a solid-liquid reaction system. Adjust the pH to 1.5-5.0, raise the temperature to 40-80℃, and add the oxidant in batches to allow the Mn... 2+ It is selectively oxidized to Mn at the solid-liquid interface. 3+ Mn 3+ The MnPO4 phase is preferentially formed by the combination with phosphate, resulting in a manganese-rich core in the particles; iron sources are added in stages, utilizing Mn 3+ with Fe 3+ The difference in ion diffusion rate in the solid lattice leads to the formation of a gradient solid solution structure with high manganese in the center and low manganese on the surface. After isothermal aging, solid-liquid separation, and washing, a phosphate precursor with both manganese and iron in the +3 valence and manganese in a radial gradient distribution is obtained. S2: The phosphate precursor and the binder are mixed to form a slurry, and small-diameter spherical particles and large-diameter spherical particles are obtained by differential spray drying. The particles are then mixed evenly to obtain precursor particles with a bimodal particle size distribution. S3: Add lithium source and carbon source to the precursor particles with bimodal particle size distribution, mix by wet stirring to make lithium uniformly adsorbed on the particle surface and form a carbon coating layer, dry to remove solvent, and obtain lithium-carbon composite powder. S4: The lithium-carbon composite powder is sintered in an inert atmosphere to obtain sintered material; S5: Cool, crush, sieve, and remove iron from the sintered material to obtain the lithium manganese iron phosphate cathode material.

[0009] In a third aspect, the present invention provides a phosphate precursor for the above-mentioned lithium manganese iron phosphate cathode material, wherein the precursor contains manganese phosphate phase MnPO4 as a particle core; the content of manganese in the precursor decreases gradually from the center to the surface along the radial direction of the particles, while the content of iron increases gradually; and both manganese and iron in the precursor exist stably in the +3 oxidation state.

[0010] The present invention has at least the following beneficial effects: (1) This invention uses a solid-liquid composite method to preferentially generate MnPO4 in situ as the manganese-rich core of the particles, and constructs a radial gradient structure of "high manganese core and low manganese shell" by staged iron supplementation. The iron-rich phase on the particle surface has a much higher chemical stability than the high manganese phase, which significantly reduces the Mn content during charging and discharging. 3+ This eliminates the risk of corrosion and dissolution when in contact with the electrolyte, while the core retains a high manganese content to maintain a high voltage platform and high energy density, fundamentally resolving the core contradiction between the traditional lithium manganese iron phosphate's "high manganese and high energy" and "easy manganese dissolution and cycle decay".

[0011] (2) Mn was locked by a three-pronged approach: selective quantitative oxidation with persulfate, complexation coordination with phosphate, and in-situ encapsulation with phosphate lattice. 3+ Completely suppress 2Mn 3+ The disproportionation side reaction ensures that Fe and Mn are stably transferred from the precursor to the finished cathode material in the +3 oxidation state, avoiding capacity loss and structural distortion caused by oxidation state fluctuations.

[0012] (3) The precursor is spray-dried in a differentiated manner to form a bimodal particle size distribution with D50 of 3~8 μm and 15~25 μm. The small particles precisely fill the gaps between the large particles. Combined with segmented high-temperature sintering to improve the density of single-particle crystals and full coverage of continuous dense multi-element carbon conductive network, the compacted density of the finished product is ≥2.45 g / cm³. 3 Meanwhile, the carbon layer significantly improves the electronic conductivity between particles.

[0013] (4) The lithium source and multiple carbon sources (two or more of pitch, glucose, carbon nanotubes, and graphene) are adsorbed and coated in the same wet process, simplifying the process. The high-temperature solid-phase lithium intercalation process does not destroy the manganese radial gradient structure, trivalent valence state and conductive carbon network, thus achieving a synergistic improvement in high energy density and long cycle stability. Attached Figure Description

[0014] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0015] Figure 1 This is an electron microscope image of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 2 This is an electron microscope image of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 3 This is an electron microscope image of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 4 This is an electron microscope image of the lithium manganese iron phosphate cathode material synthesized in Example 1 of this invention; Figure 5 This is an electron microscope image of the lithium manganese iron phosphate cathode material synthesized in Example 1 of this invention; Figure 6 This is a table showing the EDS element content of the core sites of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 7 This is the EDS energy spectrum of the core site of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 8 This is an EDS elemental surface mapping diagram of the core sites of the manganese iron phosphate precursor synthesized in Example 1 of the present invention; Figure 9 This is a table showing the EDS element content of the intermediate layer of the manganese iron phosphate precursor synthesized in Example 1 of this invention. Figure 10 This is the EDS energy spectrum of the intermediate layer site of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 11 This is an EDS elemental surface distribution (Mapping) diagram of the intermediate layer of the manganese iron phosphate precursor synthesized in Example 1 of the present invention; Figure 12 This is a table of EDS element content at the outer layer region of the manganese iron phosphate precursor synthesized in Example 1 of the present invention; Figure 13 This is the EDS energy spectrum of the outer layer region of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 14 This is an EDS elemental surface distribution (Mapping) map of the outer layer region of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 15 This is a table of EDS element content at surface sites of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 16 This is the EDS energy spectrum of the surface site of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 17 This is an EDS elemental surface distribution (Mapping) diagram of the surface sites of the manganese iron phosphate precursor synthesized in Example 1 of this invention; Figure 18 This is a comparison diagram of the XRD pattern of the manganese iron phosphate precursor prepared in Example 1 of the present invention with the standard cards of manganese phosphate and iron phosphate. Figure 19 This is a comparison of the XRD pattern of the lithium manganese iron phosphate cathode material prepared in Example 1 of this invention with a standard card. Figure 20 This is a discharge specific capacity diagram of the lithium manganese iron phosphate high-pressure positive electrode material prepared in Example 1 of the present invention at different rates; Figure 21 This is the 0.1 C discharge result of the lithium manganese iron phosphate high-pressure positive electrode material prepared in Example 1 of the present invention under different metal element doping. Figure 22 The discharge specific capacity comparison curves of the lithium manganese iron phosphate high-pressure positive electrode material prepared in Example 1 of this invention and the material prepared in Comparative Example 1 at 0.2 C are shown. Figure 23 The discharge specific capacity comparison curves at 1.0 C are shown between the high-pressure positive electrode material of lithium manganese iron phosphate prepared in Example 1 of this invention and the material prepared in Comparative Example 1. Figure 24 The capacity retention rate of the lithium manganese iron phosphate high-voltage positive electrode material prepared in Example 1 of this invention and the material prepared in the comparative example, after 200 cycles at 1 C at 25°C, is compared with that of the CR2032 coin cell. Detailed Implementation

[0016] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0017] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form includes the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0018] It should be noted that if the text uses terms such as "first" or "second", these terms are only used to distinguish similar objects and should not be interpreted as indicating or implying their relative importance, order of precedence, or implicitly indicating the number of technical features indicated. It should be understood that the data in the descriptions of "first" and "second" can be interchanged where appropriate.

[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] One aspect of the present invention provides a lithium manganese iron phosphate cathode material, comprising a lithium manganese iron phosphate matrix and a carbon layer coated on the surface of the matrix. The lithium manganese iron phosphate matrix is ​​obtained by lithiation solid-state sintering of a radially gradient phosphate precursor, wherein the phosphate precursor has a manganese phosphate phase MnPO4 as the particle core. The manganese content of the particles decreases in a gradient from the center to the surface, while the iron content increases in a gradient. The matrix consists of spherical secondary particles with a bimodal particle size distribution, composed of large particles with D50 = 15~25 μm and small particles with D50 = 3~8 μm, and the mass ratio of large particles to small particles is (1.5~7):1, for example, 1.8:1, 2.5:1, 3.3:1, 4.1:1, 5.5:1, 6.3:1, etc. In the matrix, both manganese and iron exist in the +3 oxidation state, and their molar ratio is 0.99:0.01 to 0.01:0.99, for example, 0.9:1, 5:1, 15:1, 30:1, 50:1, 65:1, 80:1, 95:1, etc., and one of the elements may even be omitted. The molar ratio of manganese and iron can be controlled by adjusting the reaction pH and the difference in solid-phase lattice diffusion rate during the reaction process. The compaction density of the cathode material of this invention can reach 2.45 g / cm³. 3 The above results show that the amount of manganese leached out during the charging and discharging process is significantly reduced.

[0021] This invention synergistically suppresses manganese leaching through a MnPO4-rich core and a radial gradient structure. The core retains a high manganese content to maintain a high voltage plateau and high energy density, while the outer iron-rich phase exhibits higher chemical stability, reducing the impact of the electrolyte on Mn. 3+ Corrosion and leaching are prevented. Furthermore, the bimodal particle size distribution (d50 = 15~25 μm large particles to 3~8 μm small particles in a mass ratio of 1.5~7:1) allows small particles to fill the gaps between large particles, reducing the powder's packing porosity and achieving a compacted density ≥2.45 g / cm³. 3 This solves the core contradiction between the traditional lithium manganese iron phosphate's "high manganese and high energy" and "easy manganese leaching and cycle decay".

[0022] To construct a continuous conductive network and improve electronic conductivity and interface stability, in some embodiments, the carbon layer is a multi-component composite carbon layer with a total carbon content of 1.5~2.5 wt%, such as 1.8 wt%, 2.1 wt%, 2.4 wt%, etc. In some embodiments, the carbon source of the multi-component composite carbon layer is selected from two or more of pitch, glucose, carbon nanotubes, and graphene.

[0023] In some embodiments, the mass ratio of large particles to small particles is (2~5):1, thereby significantly improving compaction performance.

[0024] In some embodiments, trace amounts of modified metal elements are uniformly doped into the crystal lattice of the matrix, with a total doping amount of 0.2~1.0 wt%, such as 0.4 wt% or 0.8 wt%. The trace amounts of modified metal are added simultaneously in small quantities and uniformly doped within the crystal lattice, serving to fine-tune the crystal lattice.

[0025] In some embodiments, the modified metal element is selected from one or more of Mg, Ti, Nb, and V.

[0026] In some embodiments, the modified metal elements are distributed radially without a concentration gradient. This limitation ensures that the modified metals are uniformly distributed within the crystal lattice, serving only to fine-tune the lattice and stabilize the structure, without interfering with the radial gradient function of the core manganese element ("rich in the core and rich in iron on the surface"), thus avoiding complex gradient structures and making the suppression of manganese dissolution and the high-pressure compaction effect precisely controllable.

[0027] A second aspect of the present invention provides a method for preparing the above-mentioned lithium manganese iron phosphate cathode material, comprising the following steps.

[0028] Step S1: Mix manganese, iron, and phosphorus sources with water to form a solid-liquid reaction system, adjust the pH to 1.5-5.0, raise the temperature to 40-80℃, and add the oxidant in batches to allow the Mn... 2+ It is selectively oxidized to Mn at the solid-liquid interface. 3+ Mn 3+ The MnPO4 phase is preferentially formed by the combination with phosphate, resulting in a manganese-rich core in the particles; iron sources are added in stages, utilizing Mn 3+ with Fe 3+ The difference in ion diffusion rates within the solid lattice leads to the formation of a radially gradient solid solution structure with high manganese content at the center and low manganese content at the surface. After isothermal aging, solid-liquid separation, and washing, a phosphate precursor with both manganese and iron in the +3 valence state and a radially gradient distribution of manganese is obtained. The oxidant is quantitatively and batchively oxidized to avoid localized strong oxidation. The system contains weakly acidic phosphate ions and newly formed Mn. 3+ Rapidly combining to form a stable MnPO4 coordination structure; in-situ co-crystallization at the solid-liquid interface to form a phosphate lattice, Mn 3+ + Embedded octahedral coordination sites, with dual blocking of coordination bonds and crystal steric hindrance in 2Mn3+ Disproportionation reaction, maintaining stable trivalent manganese throughout.

[0029] The stepwise reaction equations for this step are as follows: (1) Selective oxidation of divalent manganese at the solid-liquid interface

[0030] (2) Newly formed trivalent manganese preferentially combines with phosphate to form stable MnPO4 (the main phase with a manganese-rich core in the particles). Mn 3+ +PO4 3 =MnPO4 (3) Iron source is replenished in stages, Mn 3+ Fe 3+ In-situ co-crystallization forms a radial gradient solid solution (Mn-rich at the center and Fe-rich on the surface). (1 x)Mn 3+ +xFe 3+ +PO4 3 =Mn1 x Fe x PO4 This step in the process can completely suppress the disproportionation side reaction shown below in conventional trivalent manganese: 2Mn 3+ =Mn 2+ +Mn 4+ In this step, the oxidation reaction occurs at the solid-liquid interface, and the newly formed Mn 3+ MnPO4 is immediately generated as the core framework of the particles; subsequently, iron salt solution is added dropwise in stages, relying on Mn 3+ Fe 3+ The difference in ion diffusion rates creates a radial gradient structure where the Mn content continuously decreases and the Fe content continuously increases from the particle center to the surface. Trace amounts of modified metal can be added simultaneously in small quantities, uniformly doped within the crystal lattice without significant gradient changes. Utilizing the in-situ lattice encapsulation effect of phosphate, trivalent manganese is locked in place by both coordination bonding and steric hindrance, completely suppressing disproportionation.

[0031] The core objective of pH adjustment in this step is to stabilize Mn in the reaction system. 3+ To successfully generate the target phase MnPO4. Trivalent manganese ions are extremely unstable; pH is the determining factor for Mn... 3+ The key factors for stability and preventing rapid disproportionation / hydrolysis are: In the pH range of 1.5–5: phosphate buffer system to balance free PO4. 3-With the concentration of phosphoric acid added to adjust the pH of the system, the following multi-level dissociation equilibrium exists:

[0032] In a weakly acidic environment of 1.5–5, the system simultaneously contains sufficient HPO4. 2- With a small amount of free PO4 3- ; Newborn Mn 3+ Immediately after being generated, it interacts with PO4. 3- Coordination generates the MnPO4 kernel, rapidly complexing and locking Mn 3+ This prevents the disproportionation reaction from occurring.

[0033] The following fatal flaws exist when the pH is <1.5 (too acidic): (1) When the hydrogen ion concentration is too high, the dissociation of phosphate is strongly inhibited, and the free PO4 in the solution 3- The concentration is extremely low, making it impossible for Mn to bind rapidly. 3+ ; (2) Free Mn 3+ Without the protection of phosphate complexation, disproportionation occurs rapidly, leading to the formation of large amounts of easily soluble divalent manganese and manganese dioxide impurities; (3) The complete MnPO4 rich manganese core cannot be formed, the radial manganese gradient structure of the particles is completely ineffective, and the manganese dissolution in subsequent cycles increases significantly. (4) Strong acid will corrode the reactor, and excessive acid washing is costly and the wastewater has high neutralization pressure.

[0034] However, at pH > 5 (slightly acidic / near neutral), the following fatal flaw exists: (1) System H + Insufficient, PO4 3- The concentration surged, Mn 3+ Fe 3+ It will instantly and randomly precipitate in large quantities, crystallize rapidly in an explosive manner, and make it impossible to control ion diffusion in stages, thus failing to create a radial gradient of high manganese inside and low manganese outside. (2) Mn³ + It is very easy to hydrolyze to form Mn(OH)3 flocculent hydroxide impurity. After sintering, this impurity will destroy the olivine lattice, and a large amount of manganese will dissolve out during the cycle. (3) The simultaneous hydrolysis of ferric iron to generate ferric hydroxide impurities leads to a decrease in precursor purity and simultaneous deterioration of finished product compaction and cycle stability. (4) The sedimentation rate is out of control, and only irregular fine particles can be obtained. It is impossible to prepare spherical bimodal graded powder by subsequent spray drying, and the compaction density cannot meet the index.

[0035] This invention achieves precise control of ion diffusion rate by adjusting pH value, thereby realizing a manganese radial gradient: Gradient forming principle: staged iron supplementation, relying on Mn3+ Fe 3+ The difference in diffusion rates enables "core-rich Mn and shell-rich Fe"; In the pH buffer zone of 1.5 to 5, the hydrolysis rate of metal ions is slow, the ion diffusion rate is controllable, the crystal grows slowly, and a gradient shell is formed layer by layer.

[0036] If the pH deviates from the range, the precipitation rate will fluctuate, ions will not have enough time to diffuse in layers, Mn and Fe will be uniformly mixed inside the particles, there will be no radial concentration gradient, and the core structure that inhibits manganese dissolution will be lost.

[0037] This invention achieves both consideration of precursor morphology and assurance of subsequent high-pressure bimodal granulation by adjusting the pH value of the reaction system. (1) The MnPO4-based phosphate crystals generated in the reaction system at pH 1.5~5 have a moderate growth rate, moderate crystallinity, smooth particle surface, good plasticity of filter cake, and can form dense spherical secondary particles by spray drying. (2) If the pH is too low or too high, needle-like, fine, amorphous flocculent precursors will be generated. These precursors are easily broken during spray drying, and it is impossible to obtain spherical particles with controllable D50. This will cause the bimodal gradation process to fail, resulting in a significant decrease in compaction density.

[0038] The above steps of the present invention, by controlling the pH of the reaction system at 1.5~5.0, achieve the following results: (1) The weakly acidic phosphate buffer zone can maintain a suitable concentration of free phosphate, allowing the newly generated Mn to be released. 3+ Rapid coordination generates MnPO4 as a manganese-rich core for particles, thereby locking trivalent manganese through coordination and suppressing disproportionation side reactions; (2) Equilibrium persulfate oxidation potential to achieve Mn 2+ To Mn 3+ Selective directional oxidation, avoiding the formation of Mn. 4+ Impurities; (3) Smoothly regulate Mn 3+ Fe 3+ Ion diffusion and crystallization rate, staged precipitation to construct a radial gradient structure with a high manganese core and a low manganese surface; (4) Avoid pH being too low, which can lead to insufficient phosphate dissociation and Mn dissociation. 3+ The problems include severe disproportionation, excessively high pH leading to the hydrolysis of metal ions to form hydroxide impurities, and uncontrolled crystallization without gradient. (5) Obtain a phosphate precursor with regular morphology and excellent plasticity to ensure the subsequent spray drying preparation of bimodal spherical particles, so as to achieve the high compaction characteristics of the material.

[0039] Isothermal ripening allows for sufficient and stable crystal growth. Solid-liquid separation and washing with pure water yield a manganese iron phosphate precursor with a manganese-rich core (MnPO4), a radial distribution of high manganese content in the inner part and low manganese content in the outer part, and both Fe and Mn having a +3 valence. Adding a modifying metal results in a trace metal-modified manganese iron phosphate precursor, which fully retains the manganese-rich core-low manganese shell gradient structure.

[0040] The preparation method of this invention employs a fully solid-liquid composite process, with the reaction concentrated at the solid-liquid interface, unlike traditional liquid-phase co-precipitation. It preferentially generates MnPO4 manganese phosphate as the core phase, serving as a key intermediate for constructing a manganese radial gradient, stabilizing trivalent manganese, and inhibiting manganese dissolution. Multiple methods synergistically stabilize Mn. 3+ Selective controlled oxidation, phosphate complexation coordination, and phosphate lattice encapsulation; the trivalent metal valence state of the precursor can be stably transferred to the subsequent sintering process, and the manganese in the finished cathode material still maintains a +3 valence.

[0041] Step S2: The phosphate precursor and binder are mixed to form a slurry, which is then spray-dried to obtain small-diameter spherical particles and large-diameter spherical particles respectively. These are then mixed evenly to obtain precursor particles with a bimodal particle size distribution. The combination of large and small spherical particles allows the smaller particles to fill the gaps between the larger particles, reducing powder porosity and significantly improving compaction performance.

[0042] Step S3: Add lithium and carbon sources to the precursor particles with a bimodal particle size distribution. Wet mixing allows lithium to be uniformly adsorbed onto the particle surface, forming a carbon coating layer. Drying removes the solvent, yielding lithium-carbon composite powder. The lithium source and multi-element carbon source are adsorbed and coated in the same wet process, ensuring a uniform distribution of lithium on the particle surface and in the interstices. Continuous, dense carbon layer coating (especially a multi-element carbon layer) further enhances the overall compactness of the particles.

[0043] Step S4: The lithium-carbon composite powder is sintered in an inert atmosphere to obtain the sintered material. The entire process is carried out in an inert atmosphere with no redox reactions, ensuring that Fe and Mn maintain their +3 valence and preserving the radial gradient structure of manganese. Step S5: Cool, crush, sieve, and remove iron from the sintered material to obtain a lithium iron manganese phosphate cathode material with a manganese-rich core radial gradient, low manganese dissolution, and high compaction.

[0044] The technical solution of this invention uses a solid-liquid composite method to make Mn 2+ Selective oxidation to Mn at the solid-liquid interface 3+ Prioritize the generation of MnPO4 manganese-rich cores, and utilize Mn 3+ with Fe 3+The difference in ion diffusion rate constructs a radial gradient structure, with coordination bonding and lattice steric hindrance providing dual stability to the +3 valence state and suppressing disproportionation; the bimodal particle size distribution reduces packing porosity, and the simultaneous lithium-carbon coating integrated process ensures the integrity of the conductive network without disrupting the gradient structure, ultimately achieving a compaction density ≥2.45 g / cm³. 3 High-performance cathode materials with significantly reduced manganese leaching.

[0045] The core innovation of this invention is to first generate MnPO4 in situ as a high-manganese core for the particles, and then construct a radial gradient of "high-manganese core and low-manganese shell" by adding iron in stages. The iron-rich manganese phosphate lithium iron phosphate phase on the particle surface has a much higher chemical stability than the high-manganese phase, and significantly reduces Mn upon contact with the electrolyte. 3+ Corrosion leaching; the core retains high manganese components to maintain a high voltage platform and high energy density, solving the core contradiction between the traditional lithium manganese iron phosphate's "high manganese and high energy" and "easy manganese leaching and cycle decay".

[0046] In some embodiments, in step S1, the manganese source is selected from one or both of manganese tetroxide and manganese sulfate.

[0047] In some embodiments, in step S1, the iron source is a ferrous salt that can generate ferric iron, preferably one or more selected from ferrous sulfate, ferrous chloride, ferric citrate and ferrous acetate.

[0048] In some embodiments, in step S1, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, diammonium dihydrogen phosphate, and phosphoric acid.

[0049] In some embodiments, in step S1, the oxidant is persulfate.

[0050] Manganese tetroxide and manganese sulfate were selected as manganese sources, and combined with ferrous salts that can generate ferric iron (ferrous sulfate, ferrous chloride, ferric citrate, ferrous acetate), and combined with the selective oxidation of persulfate and the complexation coordination with phosphate, so that the newly generated Mn 3+ Preferentially binds to phosphate to form stable MnPO4 as the manganese-rich core of the particles, thereby completely suppressing 2Mn by locking trivalent manganese through coordination bonding and steric hindrance. 3+ The disproportionation side reaction enables the trivalent manganese structure to be stably transferred from the precursor to the finished cathode material.

[0051] In some embodiments, in step S1, the pH is adjusted to 1.5 to 5.0 using one or both of phosphoric acid and triethylamine, for example, 2.0, 2.5, 3.3, 4.1, 4.8, etc.

[0052] In some embodiments, in step S1, the amount of oxidant added is 100% to 105% of the theoretical molar amount, for example, 102% or 104%, and the feed is made by slow dripping in batches.

[0053] The pH is adjusted to a weakly acidic environment of 1.5-5.0 using phosphoric acid and / or triethylamine. Persulfate is then added slowly in batches at 100%-105% of the theoretical molar amount to avoid disproportionation of trivalent manganese caused by localized strong oxidation, ensuring the preservation of Mn. 3+ Immediately after the solid-liquid interface is formed, it combines with phosphate to generate MnPO4, providing a stable manganese-rich core framework for the subsequent construction of radial gradient structures.

[0054] In some embodiments, in step S1, the isothermal ripening time is 4~8 h, and the temperature is maintained at 40~80℃, so that the manganese iron phosphate crystals can grow and stabilize fully. At the same time, relying on the in-situ lattice encapsulation effect of phosphate, trivalent manganese is further locked, ensuring that Fe and Mn in the precursor are both stable at +3 valence, laying the foundation for the complete preservation of the radial gradient structure of manganese in the subsequent sintering process.

[0055] In some embodiments, in step S2, the adhesive additive is selected from one or both of PEG and PVA, and the amount added is 0.1 to 1 wt% of the precursor mass, for example, 0.3 wt%, 0.5 wt%, 0.8 wt%, etc.

[0056] In some embodiments, in step S2, large-diameter spherical particles and small-diameter spherical particles are mixed at a mass ratio of (1.5~7):1, for example, 1.8:1, 2.5:1, 3.3:1, 4.1:1, 5.5:1, 6.3:1, etc., preferably (2~5):1.

[0057] Large particles with a D50 of 15~25μm are mixed with small particles with a D50 of 3~8μm at a mass ratio of (1.5~7):1 (preferably 2~5:1). The small particles precisely fill the gaps between the large particles, significantly reducing the porosity of the powder. Combined with segmented high-temperature sintering, this improves the density of individual crystal particles, resulting in a compacted density of ≥2.45g / cm³. 3 .

[0058] In some embodiments, in step S3, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium hydroxide monohydrate.

[0059] In some embodiments, in step S3, the carbon source is a multi-source carbon source, selected from two or more of asphalt, glucose, carbon nanotubes, and graphene.

[0060] In some embodiments, the wet mixing process in step S3 is as follows: first, the precursor particles are pre-wetted with the dispersion solvent, then the lithium source is added in batches, and the mixture is stirred at medium speed to ensure uniform lithium adsorption; then, a premixed multi-element carbon source is added, and the mixture is stirred at medium speed followed by high speed to achieve full carbon coating. The pre-stirring speed can be low, approximately 380-680 rpm. The medium-speed stirring speed is approximately 1000-1400 rpm, and the high-speed stirring speed is approximately 1500-1800 rpm.

[0061] In some embodiments, the dispersing solvent is selected from one or both of deionized water and anhydrous ethanol, and the amount of dispersing solvent added is 30% to 60% of the precursor particles' mass, for example, 35%, 42%, 49%, 55%, etc.

[0062] In some embodiments, the lithium source is added in 2 to 3 batches, with an interval of 2 to 3 minutes between each batch.

[0063] In some embodiments, the drying temperature is 60~90℃ and the drying time is 4~8 h.

[0064] In step S3, the precursor particles are first pre-stirred and wetted with the dispersion solvent, and then lithium source is added in 2-3 batches to make lithium uniformly adsorbed on the particle surface. Subsequently, a multi-component composite carbon source (two or more of pitch, glucose, carbon nanotubes, and graphene) is added for high-speed stirring and coating to achieve uniform distribution of lithium elements and full-domain construction of a continuous and complete carbon conductive network. After solvent removal by low-temperature drying at 60-90℃ for 4-8 hours, high-temperature sintering only results in solid-phase lithium intercalation without destroying the radial gradient structure of manganese and the trivalent metal valence state.

[0065] In some embodiments, in step S4, the inert atmosphere is selected from one or both of nitrogen and argon.

[0066] In some embodiments, in step S4, sintering is performed in segments. Segmented high-temperature sintering can improve the density of single-particle crystals.

[0067] In some embodiments, in step S4, sintering involves first performing a low-temperature pre-sintering at 300-450°C for 2-4 hours to pre-carbonize the carbon source and fix the morphology of the spherical particles, followed by a high-temperature solid-state lithium intercalation sintering at 680-780°C for 6-10 hours to densify the crystals and complete the lithium intercalation reaction. The high-temperature sintering only involves solid-state lithium intercalation and does not disrupt the manganese radial gradient structure, the trivalent metal valence state, or the continuous conductive carbon network.

[0068] In some embodiments, in step S4, the heating rate during the sintering process is 2~4℃ / min, for example 2.5℃ / min, 3℃ / min, 3.6℃ / min, etc., to ensure that Fe and Mn always maintain the +3 valence, without destroying the radial gradient structure of manganese, while the continuous dense carbon layer further enhances the overall compactness and conductivity of the particles.

[0069] A third aspect of the present invention provides a phosphate precursor for preparing the above-mentioned lithium manganese iron phosphate cathode material, wherein the precursor contains manganese phosphate phase MnPO4 as the particle core; the content of manganese in the precursor decreases gradually from the center to the surface along the radial direction of the particles, while the content of iron increases gradually; both manganese and iron in the precursor exist stably in the +3 oxidation state.

[0070] The phase composition and structural characteristics of the precursor have a decisive influence on the electrochemical performance of the final cathode material. Currently, there are no reports of phosphate precursor structures using manganese phosphate (MnPO4) as an independent manganese-rich core phase, with manganese content decreasing radially from the inside out and iron content increasing accordingly. Furthermore, conventional precursor particle morphology control is limited, and the high porosity of monodisperse spherical particles results in a generally lower compaction density of the finished electrode than 2.3 g / cm³. 3 This limits further improvements in battery volumetric energy density.

[0071] The precursor of this invention uses MnPO4 as the key phase in the manganese-rich core, and constructs a radial gradient with manganese decreasing from the center to the surface and iron increasing synchronously through staged iron supplementation. This structure allows the subsequent sintered product to inherit the characteristics of "high manganese core for capacity preservation and iron-rich surface for stability," fundamentally solving the core contradiction of "high manganese, high energy" and "easy manganese leaching and cycle decay" in traditional lithium manganese iron phosphate. The surface layer of the precursor particles is an iron-rich phase, whose chemical stability is much higher than that of the high-manganese phase. When the finished product comes into contact with the electrolyte, this surface layer can significantly reduce Mn. 3+ This significantly reduces the risk of corrosion and leaching, improving battery cycle life, while the high manganese content in the core ensures a high voltage plateau and energy density. In the precursor, both Mn and Fe are stably in the +3 valence state, and the in-situ phosphate lattice encapsulation effect (coordination bonding + steric hindrance) completely suppresses Mn³ oxidation. + The disproportionation side reaction is eliminated. This stable trivalent state can be seamlessly transferred to the subsequent high-temperature sintering process, ensuring that manganese in the final cathode material remains in the +3 active valence state, avoiding capacity loss and structural distortion caused by valence state fluctuations.

[0072] In some embodiments, the precursor is prepared using a solid-liquid composite method combined with a selective oxidation process. This solid-liquid composite method combined with selective oxidation concentrates the reaction at the solid-liquid interface, generating new Mn. 3+ It immediately binds with phosphate to generate an MnPO4 core, effectively suppressing trivalent manganese disproportionation and constructing a manganese radial gradient structure.

[0073] In some embodiments, the process uses manganese tetroxide and / or manganese sulfate as the manganese source and persulfate as the oxidant. Using manganese tetroxide and / or manganese sulfate as the manganese source and persulfate as the oxidant can achieve Mn 2+ Selective quantitative oxidation, combined with phosphate coordination locking, ensures that manganese and iron in the precursor remain stable at +3 oxidation state throughout the process, providing a structural basis for subsequent low-manganese dissolution high-pressure cathode materials.

[0074] Furthermore, the limitations on doping elements in the precursor lattice and the corresponding beneficial effects are as described above.

[0075] The technical solution of the present invention will be described in detail below through specific embodiments, but the present invention is not limited to the following embodiments.

[0076] Example 1 This embodiment provides a core-rich manganese radial gradient manganese iron phosphate precursor, a low-manganese dissolution high-pressure multi-element carbon-coated manganese iron phosphate cathode material, and its preparation method, including the following steps: S1 Solid-liquid composite method for preparing phosphate precursors Ferrous sulfate (FeSO4·7H2O), phosphoric acid (H3PO4), and manganese tetroxide (Mn3O4) were added to a reaction vessel in a stoichiometric ratio (Fe:Mn:P = 0.4:0.6:1.0), and deionized water was added to form a solid-liquid mixture. The pH of the system was adjusted to 2.5 using phosphoric acid, and the temperature was raised to 60℃ with continuous stirring. Ammonium persulfate ((NH4)2S2O8) was added dropwise in batches as an oxidant, with the amount of oxidant added being 102% of the theoretical molar amount. The addition was controlled within 2 hours. After the addition was completed, the mixture was kept at 60℃ and stirred for 6 hours. After the reaction was completed, the solid and liquid phases were separated, and the mixture was washed three times with pure water to obtain a manganese iron phosphate precursor with a manganese-rich core of MnPO4, a radial distribution of high manganese content in the interior and low manganese content in the exterior, and both Fe and Mn having a +3 valence.

[0077] S2 precursor spheroidization and bimodal particle size distribution Add 0.5 wt% PEG binder to the precursor filter cake and mix with deionized water to form a homogeneous slurry. Perform differentiated spray drying in two batches: high-speed spray drying to obtain small-diameter spherical secondary particles with a D50=5 μm; and low-speed spray drying to obtain large-diameter spherical secondary particles with a D50=20 μm. Mix the large and small particles uniformly at a mass ratio of 7.5:2.5.

[0078] S3 Lithium source hybrid and multi-carbon source coating Using a bimodal mixed spherical precursor as the matrix, lithium carbonate (Li₂CO₃) was weighed according to the stoichiometric ratio (Li:(Fe+Mn)=1.05:1); a multi-component composite carbon source (asphalt and glucose mixed at a mass ratio of 1:1) was weighed according to 2.0 wt% of the total carbon in the finished product. Deionized water was used as the dispersion solvent, and its addition amount was 45% of the matrix mass. The precursor particles were first pre-stirred at low speed for 4 min, and then the solvent was added and stirred for 6 min to form a wetted slurry. Lithium carbonate was added in 3 batches, with an interval of 3 min between each batch, and stirred at medium speed for 20 min to ensure that lithium was uniformly adsorbed on the particle surface. The premixed carbon source was added, and the mixture was stirred at medium speed for 12 min and then at high speed for 40 min to achieve a continuous and complete carbon coating layer. The solvent was removed by drying in a 75℃ oven for 6 h to obtain lithium-carbon composite powder.

[0079] S4 segmented gradient inert atmosphere sintering The coated powder was placed in a nitrogen atmosphere tube furnace for segmented sintering with a heating rate of 3℃ / min throughout the process: first, it was pre-calcined at a low temperature of 380℃ for 3 h to pre-carbonize the carbon source and fix the morphology of the spherical particles; then, it was sintered at a high temperature of 730℃ for 8 h to densify the crystal and complete the lithium intercalation reaction.

[0080] S5 Finished Product Post-processing The sintered material is naturally cooled in the furnace, and then subjected to airflow crushing, sieving, and iron removal to finally obtain a multi-element carbon-coated lithium manganese iron phosphate cathode material with a manganese-rich core radial gradient, low manganese dissolution, and high compaction.

[0081] Example 2 This embodiment provides a core-rich manganese radial gradient manganese iron phosphate precursor, a low-manganese dissolution high-pressure multi-element carbon-coated manganese iron phosphate cathode material, and its preparation method, including the following steps: S1 Solid-liquid composite method for preparing phosphate precursors Ferrous chloride (FeCl2·4H2O), phosphoric acid (H3PO4), and manganese sulfate (MnSO4·H2O) were added to a reaction vessel in a stoichiometric ratio (Fe:Mn:P = 0.3:0.7:1.0), and deionized water was added to form a solid-liquid mixture. The pH of the system was adjusted to 3.0 using phosphoric acid, and the temperature was raised to 70°C with continuous stirring. Potassium persulfate (K2S2O8) was added dropwise as an oxidant in batches, with the amount of oxidant added being 105% of the theoretical molar amount. After the addition was complete, the mixture was kept at 70°C with stirring for 4 hours. After the reaction was completed, the solid and liquid phases were separated, and the mixture was washed four times with pure water to obtain the phosphate precursor.

[0082] S2 precursor spheroidization and bimodal particle size distribution Add 0.8 wt% PVA binder to the precursor filter cake and mix with deionized water to form a homogeneous slurry. Perform differentiated spray drying in two batches: high-speed spray drying to obtain small-diameter spherical secondary particles with a D50=3 μm; and low-speed spray drying to obtain large-diameter spherical secondary particles with a D50=15 μm. Mix the large and small particles at a mass ratio of 8:2 until homogeneous.

[0083] S3 Lithium source hybrid and multi-carbon source coating Using a bimodal mixed spherical precursor as the matrix, lithium hydroxide (LiOH·H2O) was weighed according to the stoichiometric ratio (Li:(Fe+Mn)=1.02:1); a multi-component composite carbon source (carbon nanotubes and glucose mixed at a mass ratio of 1:2) was weighed according to 2.5 wt% of the total carbon in the finished product. Anhydrous ethanol was used as the dispersion solvent, and the amount added was 50% of the matrix mass. The precursor particles were first pre-stirred at low speed for 5 min, and the solvent was added and stirred for 5 min to form a wetted slurry; lithium hydroxide was added in two batches, with an interval of 2 min between each batch, and stirred at medium speed for 25 min to ensure uniform adsorption of lithium; the premixed carbon source was added, and stirred at medium speed for 15 min, followed by high speed for 50 min to achieve coating; the solvent was removed by drying in a 60℃ oven for 8 h to obtain lithium-carbon composite powder.

[0084] S4 segmented gradient inert atmosphere sintering The coated powder was placed in an argon atmosphere tube furnace for segmented sintering with a heating rate of 2℃ / min throughout the process: first, it was pre-fired at a low temperature of 300℃ for 4 h; then, it was sintered at a high temperature of 680℃ for 10 h for solid-state lithium intercalation.

[0085] S5 Finished Product Post-processing Same as Example 1.

[0086] Example 3 This embodiment provides a core-rich manganese radial gradient manganese iron phosphate precursor, a low-manganese dissolution high-pressure multi-element carbon-coated manganese iron phosphate cathode material, and its preparation method, including the following steps: S1 Solid-liquid composite method for preparing phosphate precursors A composite manganese source, consisting of ferric citrate (FeC6H5O7), diammonium hydrogen phosphate ((NH4)2HPO4), and manganese tetroxide (Mn3O4) and manganese sulfate (MnSO4·H2O) mixed in a 1:1 mass ratio, was added to a reactor at a stoichiometric ratio (Fe:Mn:P=0.5:0.5:1.0). Deionized water was added to form a solid-liquid mixture. A trace amount of modified metal source tetrabutyl titanate (Ti(OC4H9)4) was added simultaneously, with the total doping amount controlled at 0.5 wt%. The pH of the system was adjusted to 1.5 using phosphoric acid, and the temperature was raised to 80℃ with continuous stirring. Ammonium persulfate was slowly added dropwise as an oxidant in batches, with the oxidant dosage being 100% of the theoretical molar amount. After the addition was complete, the mixture was kept at 80℃ and stirred for 8 hours to mature. After the reaction was completed, solid-liquid separation was performed, and the sample was washed three times with pure water to obtain a trace amount of titanium-modified manganese iron phosphate precursor. Ti was uniformly doped inside the crystal lattice with no obvious radial concentration gradient.

[0087] S2 precursor spheroidization and bimodal particle size distribution 0.1 wt% PEG binder was added to the precursor filter cake, and deionized water was added to prepare a homogeneous slurry. The slurry was then spray-dried in two batches with different diameters: high-speed spraying produced small-diameter spherical secondary particles with a D50 of 8 μm; low-speed spraying produced large-diameter spherical secondary particles with a D50 of 25 μm. The large and small particles were mixed homogeneously at a mass ratio of 7:3.

[0088] S3 Lithium source hybrid and multi-carbon source coating Using a bimodal mixed spherical precursor as the matrix, lithium acetate (CH3COOLi) was weighed according to the stoichiometric ratio (Li:(Fe+Mn)=1.08:1); a multi-component composite carbon source (graphene and pitch mixed at a mass ratio of 1:3) was weighed according to 1.5 wt% of the total carbon in the finished product. The dispersion solvent was a mixture of deionized water and anhydrous ethanol at a volume ratio of 1:1, and the amount added was 60% of the matrix mass. The precursor particles were first pre-stirred at low speed for 3 min, and the solvent was added and stirred for 8 min to form a wetted slurry; lithium acetate was added in 3 batches, with an interval of 2 min between each batch, and stirred at medium speed for 15 min to ensure uniform lithium adsorption; the premixed carbon source was added, and stirred at medium speed for 10 min, followed by high speed for 30 min to achieve coating; the solvent was removed by drying in a 90℃ oven for 4 h to obtain lithium-carbon composite powder.

[0089] S4 segmented gradient inert atmosphere sintering The coated powder was placed in a nitrogen atmosphere tube furnace for segmented sintering with a heating rate of 4℃ / min throughout the process: first, it was pre-fired at a low temperature of 450℃ for 2 h; then, it was sintered at a high temperature of 780℃ for 6 h for solid-state lithium intercalation.

[0090] S5 Finished Product Post-processing Same as Example 1.

[0091] Example 4 This embodiment provides a core-rich manganese radial gradient manganese iron phosphate precursor, a low-manganese dissolution high-pressure multi-element carbon-coated manganese iron phosphate cathode material, and its preparation method, including the following steps: S1 Solid-liquid composite method for preparing phosphate precursors Ferrous acetate (Fe(CH3COO)2), phosphoric acid (H3PO4), and manganese sulfate (MnSO4·H2O) were added to a reactor in a stoichiometric ratio (Fe:Mn:P = 0.35:0.65:1.0), and deionized water was added to form a solid-liquid mixture. Trace amounts of modified metal sources, magnesium nitrate (Mg(NO3)2) and zirconium nitrate (Zr(NO3)4), were added simultaneously, with the total doping amount controlled at 0.8 wt%. The pH of the system was adjusted to 4.0 using phosphoric acid, and the temperature was raised to 50℃ with continuous stirring. Sodium persulfate (Na2S2O8) was added dropwise in batches as an oxidant, with the oxidant dosage being 103% of the theoretical molar amount. After the addition was complete, the mixture was kept at 50℃ and stirred for 5 h. After the reaction was complete, the solid and liquid phases were separated, and the mixture was washed three times with pure water to obtain the magnesium- and zirconium-modified manganese iron phosphate precursor.

[0092] S2 precursor spheroidization and bimodal particle size distribution Add 0.3 wt% PVA binder to the precursor filter cake and mix with deionized water to form a homogeneous slurry. Perform differentiated spray drying in two batches: high-speed spray drying to obtain small-diameter spherical secondary particles with a D50=6 μm; and low-speed spray drying to obtain large-diameter spherical secondary particles with a D50=18 μm. Mix the large and small particles uniformly at a mass ratio of 7.5:2.5.

[0093] S3 Lithium source hybrid and multi-carbon source coating Using a bimodal mixed spherical precursor as the matrix, lithium carbonate was weighed according to the stoichiometric ratio (Li:(Fe+Mn)=1.05:1); a multi-component composite carbon source (glucose and carbon nanotubes mixed at a mass ratio of 2:1) was weighed according to 2.2 wt% of the total carbon in the finished product. Deionized water was used as the dispersion solvent, and the amount added was 35% of the matrix mass. The precursor particles were first pre-stirred at low speed for 4 min, and the solvent was added and stirred for 7 min to form a wetted slurry; lithium carbonate was added in 3 batches, with an interval of 3 min between each batch, and stirred at medium speed for 22 min to ensure uniform lithium adsorption; the premixed carbon source was added, and stirred at medium speed for 13 min, followed by high speed for 45 min to achieve coating; the solvent was removed by drying in an oven at 80℃ for 5 h to obtain lithium-carbon composite powder.

[0094] S4 segmented gradient inert atmosphere sintering The coated powder was placed in an argon atmosphere tube furnace for segmented sintering with a heating rate of 3℃ / min throughout the process: first, it was pre-fired at a low temperature of 400℃ for 3 h; then, it was sintered at a high temperature of 750℃ for 7 h for solid-state lithium intercalation.

[0095] S5 Finished Product Post-processing Same as Example 1.

[0096] Comparative Example 1 This comparative example uses a traditional liquid-phase co-precipitation method to prepare the manganese iron phosphate precursor. The specific steps are as follows: Ferrous sulfate, manganese sulfate, and phosphoric acid were dissolved in deionized water in a stoichiometric ratio (Fe:Mn:P = 0.4:0.6:1.0) to form a homogeneous solution. The pH was adjusted to 7.0 with ammonia, and the mixture was stirred at 60°C for 6 h to co-precipitate the manganese-iron phosphate precursor. This precursor exhibited a uniform distribution of Mn and Fe elements, lacked a radial gradient structure of manganese, and did not contain a manganese-rich MnPO4 core phase. Subsequent steps S2 to S5 were the same as in Example 1.

[0097] Testing showed that, under the same charge-discharge conditions, the manganese leaching amount of the cathode material obtained in Comparative Example 1 was 10 ppb, significantly higher than that in Examples 1-4 (less than 1 ppb, i.e., less than the detection limit), and the cycle capacity retention was significantly lower than that in the examples; the compaction density was approximately 2.15 g / cm³. 3 The concentration was lower than ≥2.45 g / cm³ in the example. 3 The compaction density of the examples is 2.50~2.60 g / cm³. 3 Within the range.

[0098] The precursor materials and cathode materials prepared in the above embodiments and comparative examples are subjected to relevant performance tests, such as compaction density test, cycle capacity retention test, and manganese leaching test.

[0099] The following describes some performance characterization methods used in this invention. Where specific test methods are not given, conventional test methods in the field shall apply.

[0100] (1) Compacted density test The prepared dried lithium manganese iron phosphate positive electrode active powder was filled into a standard mold and pressed into a sheet using a powder compaction tester under a fixed pressure. The mass of the pressed sheet was weighed and the volume of the pressed sheet was measured. The compaction density of the material was calculated.

[0101] (2) Cyclic capacity retention test The prepared lithium manganese iron phosphate cathode material was dispersed in a solvent with conductive carbon and binder in a certain mass ratio to form a cathode slurry. This slurry was coated onto an aluminum foil current collector, and then dried, rolled, and cut to obtain the cathode sheet. A CR2032 coin cell lithium-ion battery was assembled using a lithium metal sheet as the counter electrode and a polyolefin separator. The coin cell was placed in a constant temperature environment at 25°C, and the charge / discharge voltage range was set to 2.5~4.3 V (vs Li / Li). +Charge-discharge cycle tests are conducted according to the preset rate regime; the capacity retention rate after a specified number of cycles is calculated based on the initial discharge capacity.

[0102] (3) Manganese leaching test CR2032 coin cell lithium-ion batteries were assembled using the same process described above, and tested at 25°C and 2.5~4.3 V (vs Li / Li). + The predetermined number of charge-discharge cycles were completed within the charge-discharge window. After the test, the battery was disassembled in an argon glove box with an oxygen content of <0.1 ppm, and the electrolyte inside the cell was collected. The electrolyte was filtered through a 0.22 μm organic phase filter membrane and acidified with dilute nitric acid to a fixed volume. The manganese concentration in the electrolyte was determined using inductively coupled plasma mass spectrometry (ICP-MS), and the manganese dissolution amount of the lithium manganese iron phosphate material was calculated. The internal standard method was used to correct for matrix effects and eliminate test interference caused by the coexistence of iron in the system. The detection limit of the ICP-MS instrument used for manganese was <1 ppb.

[0103] The gradient structure manganese iron phosphate precursor particles prepared in Example 1 were characterized by SEM-EDS. Figures 1 to 3 The images show SEM images of the samples (magnifications of 500, 5000, and 50000x, with scale bars of 200 μm, 20 μm, and 2 μm, respectively). As can be seen from the images, the precursor samples prepared in this invention have primary grains that are roughly rectangular plates with clear grain outlines and a relatively uniform overall grain size distribution, although a small amount of grain agglomeration exists.

[0104] Figure 6 , Figure 7 , Figure 8 EDS characterization results for the test sites in the core of the precursor particle material; Figure 7 The EDS energy spectrum of the core site shows characteristic energy peaks of O, P, Mn and V elements, but no obvious characteristic peaks of foreign impurity elements. Figure 6 Semi-quantitative EDS results of the core sites confirmed that the core matrix mainly contains O, P, and Mn elements, and contains trace amounts of V dopant. Figure 8 The EDS elemental mapping diagram in the core region shows that the matrix elements O, P, and Mn are continuously and uniformly distributed in the particle core region, while the dopant element V is dispersed throughout the entire particle range.

[0105] Figures 9, 10, and 11 show the EDS characterization results of the intermediate layer test points of the precursor particles. Figure 10 The intermediate layer EDS energy spectrum shows characteristic energy peaks for all elements, including O, P, Mn, Fe, and V, with no obvious characteristic peaks for foreign impurities. Figure 9The semi-quantitative elemental composition results of the intermediate layer EDS in the table show that the intermediate layer contains Mn, Fe metal components, and trace amounts of V doping. Comparison of the EDS test data of the core and intermediate layer reveals that, compared to the core region, the proportion of manganese in the intermediate layer decreases, while the proportion of iron significantly increases. Figure 11 The image shows the surface distribution of EDS elements in the middle region, displaying the diffuse distribution of O, P, Mn, Fe, and V elements in the test area.

[0106] Figures 12, 13, and 14 show the EDS characterization results of the test points on the outer layer of the precursor particles. Figure 13 The outer EDS energy spectrum can identify the characteristic energy peaks corresponding to O, P, Mn, Fe and V elements, and there are no obvious characteristic peaks of foreign impurity elements. Figure 12 The EDS semi-quantitative test results of the outer layer sites show that the iron content in the outer layer region further increases, while the manganese content continues to decrease compared to the middle layer, and it also contains trace amounts of V doping components. Figure 14 The image shows the surface distribution mapping of EDS elements in the outer region, indicating that O, P, Mn, Fe, and V elements are dispersed throughout the test area.

[0107] Figures 15, 16, and 17 show the EDS characterization results of the surface test sites of the precursor particles. Figure 16 shows the EDS energy spectrum of the surface sites, which exhibits characteristic energy peaks for O, P, Mn, and Fe elements, but no obvious characteristic peaks for foreign impurity elements. Figure 15 The semi-quantitative EDS elemental content test results at the surface points of the table show that the iron content is highest at the surface of the precursor particles, while the manganese content further decreases. Figure 17 is a surface distribution mapping of EDS elements in the surface region, indicating that O, P, Mn, and Fe elements are diffusely distributed in the test area.

[0108] Based on the multi-point EDS comparative test results at different depths in the core, intermediate layer, outer layer, and surface layer of the particles, it can be seen that the manganese-iron phosphate precursor particle material prepared in this invention has a gradient distribution structure of elemental composition. The core region of the particles is rich in manganese, and the manganese content gradually decreases while the iron content gradually increases from the core to the surface layer. SEM-EDS characterization is only used for observation of the microscopic morphology of the samples, elemental qualitative analysis, and analysis of the elemental distribution trend in micro-areas. The overall precise stoichiometric composition of the material is determined by ICP method.

[0109] This invention modifies lithium iron phosphate (LFP) crystals by introducing metal ion doping into the gradient structure olivine-manganese phosphate lattice. The M-sites of the transition metal in the olivine structure can accommodate doped cations with matching ionic radii, replacing the Mn atoms within the lattice. 2+ / Fe 2+ Optimize crystal structure and lithium-ion transport kinetics to suppress manganese dissolution and improve cycle and rate performance. Mg 2+As an alkaline earth metal equivalent dopant, it can occupy the M site of transition metals and suppress Mn by relying on a rigid ionic framework. 3+ The induced Jahn-Teller distortion stabilizes the crystal structure, reduces lattice defects and manganese ion dissolution, and optimizes lithium-ion diffusion channels. Vanadium, niobium, and titanium are high-valence heterovalent dopants of transition metals, occupying the M sites of the transition metals. The substitution of divalent metal ions by high-valence ions induces controllable vacancy defects in the lattice, improving the intrinsic electronic conductivity of the material, while simultaneously regulating cell stress and protecting the gradient structure of the Mn / Fe transition from the inside to the outside of the particles. The ionic radii of magnesium, vanadium, niobium, and titanium are all compatible with olivine transition metal sites. Although the doping mechanisms differ, they are all commonly used lattice modification elements in the lithium manganese iron phosphate system. Based on the gradient matrix structure and doping mechanism disclosed in this invention, those skilled in the art can reasonably expect that magnesium, niobium, and titanium doping can also achieve performance improvement. This application only completed the complete microscopic and electrochemical characterization of the vanadium-doped sample, while also completing the electrochemical testing of the magnesium and niobium-doped samples, verifying the universality of this modification scheme.

[0110] The cathode material prepared in Example 1 was characterized by SEM morphology. Figure 4 and Figure 5 These are SEM images of the lithium manganese iron phosphate cathode material synthesized in Example 1 at different magnifications. The low-magnification SEM image (Figure 4) shows that the powder consists of numerous spherical secondary particles with good particle dispersion; the high-magnification SEM image (Figure 5) shows that the secondary particles have regular morphology and are nearly spherical. Figure 4 It can be seen that the appropriate ratio of large and small spheres in the cathode material synthesized in this invention is beneficial for improving the compaction density. Near-spherical particles facilitate dense powder packing, resulting in a compaction density of up to 2.55 g / cm³. 3 .

[0111] Figure 18 The XRD pattern of the manganese-iron phosphate precursor prepared in Example 1 is compared with the diffraction peak positions of the standard phases PDF#29-0891 (manganese phosphate) and PDF#29-0715 (iron phosphate). As can be seen from the figure, the manganese-iron phosphate precursor sample prepared in this invention does not exhibit characteristic diffraction peaks of independent manganese phosphate and iron phosphate phases. Manganese and iron metal ions uniformly enter the olivine-type crystal lattice to form a single solid solution phase without phase separation. The results demonstrate that this invention successfully synthesizes an olivine-type single-phase solid solution manganese-iron phosphate material with good crystallinity and no obvious impurity phase formation.

[0112] Figure 19The image shows the X-ray diffraction pattern of the gradient structure lithium manganese iron phosphate cathode material of this invention. As can be seen from the image, all characteristic diffraction peaks of the sample prepared in this invention are well matched with the characteristic peak positions of Li(Mn, Fe)PO4 on the standard card PDF#33-0802. The diffraction peaks are sharp, the baselines are stable, and there are no obvious impurity peak signals, proving that this invention has successfully synthesized the target lithium manganese iron phosphate cathode material.

[0113] Figure 20 The discharge curves of the lithium manganese iron phosphate high-density cathode material prepared in Example 1 are shown at different rates of 0.1 C, 0.2 C, 0.5 C, and 1.0 C. As the charge / discharge rate increases from 0.1 C to 1.0 C, the discharge specific capacity of the material shows a slight decrease. The discharge specific capacity reaches 158 mAh / g at 0.1 C and still maintains 144 mAh / g at 1.0 C, demonstrating good rate performance. The discharge plateau characteristics are clear at different rates, and the polarization increase is controllable.

[0114] Figure 21 shows a comparison of the 0.1 C discharge curves of lithium manganese iron phosphate cathode materials modified with different metal elements. As can be seen from the figure, the vanadium-doped sample has a discharge specific capacity of 160 mAh / g, which is higher than that of the niobium-doped and magnesium-doped samples. This indicates that vanadium doping is more beneficial for improving the reversible discharge capacity of lithium manganese iron phosphate materials.

[0115] Figure 22 The curves show the discharge specific capacity comparison between the lithium manganese iron phosphate cathode material prepared in Example 1 and the material prepared in Comparative Example 1 at 0.2 C. Figure 23 The curves show the discharge specific capacity comparison between the lithium manganese iron phosphate cathode material prepared in Example 1 and the material prepared in Comparative Example 1 at 1.0 C.

[0116] Combining the discharge curves at 0.2 C and 1.0 C in these two figures, it can be seen that the specific capacity of the cathode material prepared by this invention at both rates (approximately 155 mAh / g and 143 mAh / g) is higher than that of the comparative example (approximately 144 mAh / g and 138 mAh / g), and the discharge voltage plateau is higher throughout the process, indicating that it has less polarization and better kinetic performance. Furthermore, the material of this invention maintains a higher discharge voltage plateau even at high rates, demonstrating that the gradient component structure of this invention can effectively reduce polarization, improve the high-rate lithium insertion / extraction capability, and enhance the overall capacity and voltage, thus verifying the effectiveness of the product and method of this invention.

[0117] Figure 24The figure shows the capacity retention of the lithium manganese iron phosphate cathode material prepared in Example 1 and the material prepared in the comparative example after 200 cycles at 1 C at 25°C. As can be seen from the comparison between the embodiments of the present invention and the comparative example, the material prepared in the embodiments of the present invention has a higher initial capacity, and after 200 cycles, the capacity retention is over 98%, significantly better than the comparative example (approximately 90%). Furthermore, the capacity decay is more gradual, demonstrating better structural stability, longer cycle life, and significant advantages in electrochemical performance.

[0118] In the above embodiments, all raw materials were commercially available analytical grade reagents; the obtained cathode material had Mn and Fe stable at +3 valence and fully retained the radial gradient structure of "high manganese core and low manganese shell", which combined high energy density and long cycle stability.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium manganese iron phosphate cathode material, comprising a lithium manganese iron phosphate matrix and a carbon layer coated on the surface of the matrix, characterized in that, The lithium manganese iron phosphate matrix is ​​prepared by lithiation solid-state sintering of a radial gradient phosphate precursor. The phosphate precursor has a manganese phosphate phase MnPO4 as the particle core. The manganese content of the particles decreases in a gradient from the center to the surface, while the iron content increases in a gradient. The matrix consists of spherical secondary particles with a bimodal particle size distribution, composed of large particles with D50=15~25 μm and small particles with D50=3~8 μm, with a mass ratio of large particles to small particles of (1.5~7):

1. In the matrix, both manganese and iron exist in the +3 oxidation state and their molar ratio is 0.99:0.01~0.01:0.

99.

2. The lithium manganese iron phosphate cathode material according to claim 1, characterized in that, The carbon layer is a multi-component composite carbon layer with a total carbon content of 1.5~2.5 wt%. Preferably, the carbon source of the multi-component composite carbon layer is selected from two or more of asphalt, glucose, carbon nanotubes, and graphene; Preferably, the mass ratio of the large particles to the small particles is (2~5):

1.

3. The lithium manganese iron phosphate cathode material according to claim 1 or 2, characterized in that, The matrix is ​​uniformly doped with trace amounts of modified metal elements in its crystal lattice, with a total doping amount of 0.2~1.0 wt%; Preferably, the modified metal element is selected from one or more of Mg, Ti, Nb, and V; Preferably, the modified metal element is distributed without a concentration gradient along the radial direction of the particle.

4. A method for preparing the lithium manganese iron phosphate cathode material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1: Mix manganese, iron, and phosphorus sources with water to form a solid-liquid reaction system. Adjust the pH to 1.5-5.0, raise the temperature to 40-80℃, and add the oxidant in batches to allow the Mn... 2+ It is selectively oxidized to Mn at the solid-liquid interface. 3+ Mn 3+ The MnPO4 phase is preferentially formed by the combination with phosphate, resulting in a manganese-rich core in the particles; iron sources are added in stages, utilizing Mn 3+ with Fe 3+ The difference in ion diffusion rate in the solid lattice leads to the formation of a gradient solid solution structure with high manganese in the center and low manganese on the surface. After isothermal aging, solid-liquid separation, and washing, a phosphate precursor with both manganese and iron in the +3 valence and manganese in a radial gradient distribution is obtained. S2: The phosphate precursor and the binder are mixed to form a slurry, and small-diameter spherical particles and large-diameter spherical particles are obtained by differential spray drying. The particles are then mixed evenly to obtain precursor particles with a bimodal particle size distribution. S3: Add lithium source and carbon source to the precursor particles with bimodal particle size distribution, mix by wet stirring to make lithium uniformly adsorbed on the particle surface and form a carbon coating layer, dry to remove solvent, and obtain lithium-carbon composite powder. S4: The lithium-carbon composite powder is sintered in an inert atmosphere to obtain sintered material; S5: Cool, crush, sieve, and remove iron from the sintered material to obtain the lithium manganese iron phosphate cathode material.

5. The preparation method according to claim 4, characterized in that, In step S1, the manganese source is selected from one or two of manganese tetroxide and manganese sulfate; Preferably, the iron source is a ferrous salt that can generate ferric iron, and is preferably selected from one or more of ferrous sulfate, ferrous chloride, ferric citrate and ferrous acetate; Preferably, the phosphorus source is selected from one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and phosphoric acid; Preferably, the pH is adjusted to 1.5-5.0 using one or both of phosphoric acid and triethylamine; Preferably, the oxidant is persulfate; Preferably, the amount of oxidant added is 100% to 105% of the theoretical molar amount, and the feed is carried out by slow dripping in batches; Preferably, the constant temperature curing time is 4~8 hours, and the temperature is maintained at 40~80℃.

6. The preparation method according to claim 4 or 5, characterized in that, In step S2, the adhesive additive is selected from one or both of PEG and PVA, and the amount added is 0.1~1 wt% of the precursor mass. Preferably, the large-diameter spherical particles and the small-diameter spherical particles are mixed in a mass ratio of (1.5~7):1, more preferably (2~5):

1.

7. The preparation method according to any one of claims 4 to 6, characterized in that, In step S3, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate, lithium acetate, and lithium hydroxide monohydrate; Preferably, the carbon source is a multi-source carbon source, selected from two or more of asphalt, glucose, carbon nanotubes, and graphene; Preferably, the specific operation of the wet stirring and mixing is as follows: first, the precursor particles and the dispersion solvent are pre-stirred and wetted, then the lithium source is added in batches, and the mixture is stirred at medium speed to make the lithium uniformly adsorbed; then, the premixed multi-element carbon source is added, and the mixture is stirred at medium speed and then at high speed to achieve full-domain carbon coating. Preferably, the dispersing solvent is selected from one or both of deionized water and anhydrous ethanol, and the amount of the dispersing solvent added is 30% to 60% of the precursor particles mass; Preferably, the lithium source is added in 2 to 3 batches, with an interval of 2 to 3 minutes between each batch; Preferably, the drying temperature is 60~90℃ and the drying time is 4~8 h.

8. The preparation method according to any one of claims 4 to 7, characterized in that, In step S4, the inert atmosphere is selected from one or both of nitrogen and argon; Preferably, the sintering is segmented sintering; Preferably, the sintering is performed by first pre-firing at 300-450°C for 2-4 hours, and then by high-temperature solid-state lithium intercalation sintering at 680-780°C for 6-10 hours. Preferably, the heating rate during the sintering process is 2~4℃ / min.

9. A phosphate precursor for preparing the lithium manganese iron phosphate cathode material according to any one of claims 1 to 3, characterized in that, The precursor contains manganese phosphate phase MnPO4 as the particle core; the manganese content decreases gradually from the center to the surface of the particle radially, while the iron content increases gradually; both manganese and iron exist stably in the +3 oxidation state in the precursor.

10. The phosphate precursor according to claim 9, characterized in that, The precursor was prepared using a solid-liquid composite method combined with a selective oxidation process. Preferably, the process uses manganese tetroxide and / or manganese sulfate as the manganese source and persulfate as the oxidant; Preferably, the precursor's crystal lattice is uniformly doped with trace amounts of modified metal elements, with a total doping amount of 0.2~1.0 wt%. Preferably, the modified metal element is selected from one or more of Mg, Ti, Nb, and V; Preferably, the modified metal element is distributed without a concentration gradient along the radial direction of the particle.